2018
DOI: 10.1103/physreve.97.032705
|View full text |Cite
|
Sign up to set email alerts
|

Electroclinic effect in the chiral lamellarαphase of a lyotropic liquid crystal

Abstract: In thermotropic chiral Sm-A^{*} phases, an electric field along the smectic layers breaks the D_{∞} symmetry of the Sm-A^{*} phase and induces a tilt of the liquid crystal director. This so-called electroclinic effect (ECE) was first reported by Garoff and Meyer in 1977 and attracted substantial scientific and technological interest due to its linear and submicrosecond electro-optic response [S. Garoff and R. B. Meyer, Phys. Rev. A 19, 338 (1979)0556-279110.1103/PhysRevA.19.338]. We now report the observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Since phospholipid cell membranes are in a fluid L * state, this observation might also have certain implications in biophysics. The electroclinic effect in the L α * phase, thus shows all signatures of the electroclinic effect in thermotropic SmA* phases, namely the effect (i) is chiral in nature, (ii) is essentially linear in the sign and magnitude of the electric field, and (iii) shows Curie-Weiss-like behavior in the pretransitional regime of a tilting transition into lyo-SmC* [69]. Beyond these striking similarities between the electroclinic effects in SmA* and L α * there are also specific deviations, namely, the slow decay of the electro-optic response in Figure 24b, after switching and the non-linearity at low field strength in Figure 24a.…”
Section: Electroclinic Effectmentioning
confidence: 88%
See 4 more Smart Citations
“…Since phospholipid cell membranes are in a fluid L * state, this observation might also have certain implications in biophysics. The electroclinic effect in the L α * phase, thus shows all signatures of the electroclinic effect in thermotropic SmA* phases, namely the effect (i) is chiral in nature, (ii) is essentially linear in the sign and magnitude of the electric field, and (iii) shows Curie-Weiss-like behavior in the pretransitional regime of a tilting transition into lyo-SmC* [69]. Beyond these striking similarities between the electroclinic effects in SmA* and L α * there are also specific deviations, namely, the slow decay of the electro-optic response in Figure 24b, after switching and the non-linearity at low field strength in Figure 24a.…”
Section: Electroclinic Effectmentioning
confidence: 88%
“…A first indication was the observation by Jakli et al that the chirality of phospholipids makes fluid lamellar phases piezoelectric [67,68]. The discovery of the lyo-SmC* phase however sheds new light on this issue: in 2017 Harjung et al observed an electroclinic response in the L α * phase of the amphiphile 4 with 23 wt% formamide at temperatures close to its transition into the newly discovered lyo-SmC* phase [69]. The samples were poured into a liquid crystal cell and a square-wave electric field was applied to its transparent ITO electrodes (Figure 24a).…”
Section: Electroclinic Effectmentioning
confidence: 99%
See 3 more Smart Citations